STRATEGI REFORMASI BIROKRASI OLEH PENGADILAN AGAMA PEKANBARU DALAM MEMPERTAHANKAN PREDIKAT ZONA INTEGRITAS WILAYAH BEBAS KORUPSI (WBK) TAHUN 2022 - Prayoga, Dian; Harirah, Zulfa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
The current government is directing all agencies in Indonesia to implement the Integrity Zone throughout all government institutions. While many agencies have declared their commitment to the Integrity Zone, it often remains a mere formality. Consequently, these agencies remain at the declaration stage and do not attain the Corruption-Free Zone (WBK) predicate. However, the Religious Court of Pekanbaru, within a year of applying for WBK, immediately obtained the WBK predicate and has maintained it since. This research aims to understand the Bureaucratic Reform Strategy of the Religious Court of Pekanbaru in Maintaining the Integrity Zone WBK Predicate in 2022. The research is located at the Religious Court of Pekanbaru. This study employs Sedarmayanti's theory on bureaucratic reform strategies aligned with the assessment indicators for the development of integrity zones as outlined in the Regulation of the Minister of Administrative and Bureaucratic Reform Number 90 of 2021. It utilizes a qualitative descriptive approach with data collection techniques including interviews and documentation. The research findings indicate that the strategies of the Religious Court of Pekanbaru are in line with the directives of Regulation Number 90 of 2021. Pekanbaru Religious Court, in maintaining the WBK Integrity Zone predicate in 2022, adheres to all provisions outlined in Regulation Number 90 of 2021. The Institutional Arrangement Strategy focuses on the process of change within the governance and governmental organization systems aimed at enhancing effectiveness, efficiency, adaptability, and innovation. The Administrative Arrangement Strategy emphasizes improving the performance of civil servants to become effective and efficient. The Human Resources Arrangement Strategy focuses on enhancing the quality of human resources, ensuring that they are qualified and productive in carrying out their duties. The Accountability Strategy concentrates on the process of accounting for the results of performance or programs implemented. Lastly, the Public Service Strategy focuses on improving public services provided and the outcomes of the performance carried out by civil servants. Keywords: Strategy, Integrity Zone, Corruption-Free Zone.